2019
DOI: 10.1016/j.jcot.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Normal CRP and WBC values in total hip arthroplasty (THA) with signs of loosening. Do we need a joint aspiration?

Abstract: Purpose: Overall Total hip arthroplasty (THA) is a very successful procedure. However, in case of complication dedicated management is required. Two major complications of THA failures are aseptic loosening (AL) and periprosthetic joint infection (PJI). The primary hypothesis of this study was that joint aspirations in patients with signs of loosening after THA are capable to detect PJI in suspected AL with negative serologic testing. Methods: In this study a total of 108 symptomatic patients with radiographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…These controversial results may be a result of different follow-up-times and inhomogeneous study designs. In contrast to most other studies, in the current study all THA and TKA patients were undergoing the same diagnostic algorithm for AL according to Schiffner et al 15 The impact of tobacco use on the incidence of AL and implant survival time is discussed controversially in literature. Meldrum et al 17 reported a significantly higher rate of component revision with shorter survival time in THA in smokers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These controversial results may be a result of different follow-up-times and inhomogeneous study designs. In contrast to most other studies, in the current study all THA and TKA patients were undergoing the same diagnostic algorithm for AL according to Schiffner et al 15 The impact of tobacco use on the incidence of AL and implant survival time is discussed controversially in literature. Meldrum et al 17 reported a significantly higher rate of component revision with shorter survival time in THA in smokers.…”
Section: Discussionmentioning
confidence: 93%
“…The diagnosis of AL was suspected in cases with a periimplant lucency of greater than 2 mm 14 in serial anteroposterior and lateral radiographs in absence of local or systemic signs of an infection. Diagnosis was confirmed by the serologic parameter CRP within normal https://doi.org/10.1016/j.jor.2019.03.018 Received 27 January 2019; Accepted 31 March 2019 T limits in combination with a negative result of a microbiologic testing of a synovial fluid aspiration according to Schiffner et al 15 These tests were performed in all patients. To allow a retrospective control of the diagnosis soft tissue samples were obtained in all cases during the revision surgery and were subjected to a microbiological analysis.…”
Section: Methodsmentioning
confidence: 97%
“…With regard to MSIS minor criteria, current research demonstrates both promising and disappointing results. Methods using the detection of biomarkers indicative of an inflammatory response to an infection can be inconclusive at differentiating PJI from aseptic loosening [18,19]. Such biomarkers, measured in the serum and synovial fluid, include CRP detection, leukocyte counts and differential, and measurement of interleukin (IL)-6 levels.…”
Section: Msismentioning
confidence: 99%
“…Studies have shown that CRP cannot stand alone as a diagnostic tool for distinguishing PJI, but it is helpful when paired with other inflammatory markers. Schiffner et al [19] found that at the 1 mg/dL threshold for CRP, there was a 65% sensitivity and a 56% specificity. When CRP is measured from synovial fluid, sensitivity and specificity both increase to 88% and 82%, respectively, suggesting that synovial CRP may be a better diagnostic test for PJI than serum CRP.…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation